Adult exposure to ocean acidification is maladaptive for larvae of the Sydney rock oyster Saccostrea glomerata in the presence of multiple stressors. (February 2017) - Parker, Laura M.; O'Connor, Wayne A.; Byrne, Maria; Coleman, Ross A.; Virtue, Patti; Dove, Michael; Gibbs, Mitchell; Spohr, Lorraine; Scanes, Elliot; Ross, Pauline M.
Abstract : Parental effects passed from adults to their offspring have been identified as a source of rapid acclimation that may allow marine populations to persist as our surface oceans continue to decrease in pH. Little is known, however, whether parental effects are beneficial for offspring in the presence of multiple stressors. We exposed adults of the oyster Saccostrea glomerata to elevated CO2 and examined the impacts of elevated CO2 (control = 392; 856 µatm) combined with elevated temperature (control = 24; 28°C), reduced salinity (control = 35; 25) and reduced food concentration (control = full; half diet) on their larvae. Adult exposure to elevated CO2 had a positive impact on larvae reared at elevated CO2 as a sole stressor, which were 8% larger and developed faster at elevated CO2 compared with larvae from adults exposed to ambient CO2 . These larvae, however, had significantly reduced survival in all multistressor treatments. This was particularly evident for larvae reared at elevated CO2 combined with elevated temperature or reduced food concentration, with no larvae surviving in some treatment combinations. Larvae from CO2 -exposed adults had a higher standard metabolic rate. Our results provide evidence that parental exposure to ocean acidification may be maladaptive when larvae experience multiple stressors.